Effects of intensification and pasture integration on carcass traits and meat quality in Nellore cattle - Silva, Gabriele Voltareli da (2023)
The world livestock sector has the challenge to adapt to environmental and economic changes, facing the growing demand for food, improving productivity and quality of animal products. The aim of this study was to identify the most productive pasture-based production systems with GHG mitigating potentials and evaluate whether there were changes in carcass characteristics and meat quality of Nellore steers. The work was conducted between September 2019 and September 2021, at Embrapa Pecuária Sudeste, in São Carlos, SP. Fifty-eight uncastrated male Nellore steers with 280 ± 54.5 kg of live weight and 15 to 16 months of age were distributed in five treatments with two repetitions: 1) irrigated pasture of Megathyrsus maximus cv. Tanzania under intensive management with high stocking rate overseeded with oats and ryegrass in the dry and cool season (IHS); 2) rainfed pasture of M. maximus cv. Tanzania under intensive management with high stocking rate (RHS); 3) rainfed pasture with a mixture of Urochloa decumbens Stapf cv. Basilisk and U. brizantha (Hochst ex A. Rich) Stapf cv. Marandu, with moderate stocking rate (RMS); 4) livestock-forest system with U. decumbens cv. Basilisk and native Brazilian trees with moderate stocking rate (LFS) and 5) degraded pasture of U. decumbens cv. Basilisk (DP). The stocking rate was adjusted by the “put and take” technique, animal performance was monitored, CH4 emission estimated by the sulfur hexafluoride (SF6) tracer gas technique and dry matter intake (DMI) determined using internal (iNDF indigestible neutral detergent fiber) and external (TiO2 - titanium dioxide) markers. At the end of the experiment the animals were transported to the slaughterhouse-school of the University of São Paulo, in Pirassununga, SP. Before slaughter, the animals were kept in solid fasting for 16 hours, receiving water ad libitum. Hot carcass weight (HCW) were determined and then cooled at 1ºC for 24 hours. The left halves of the carcasses were weighed and deboned, and the meat was sampled between the 12th and 13th ribs to measure the ribeye area (REA), backfat thickness (BFAT), marbling score (MS) and carcass edible portion (CEP), as well as sensory analysis. The data were submitted to variance analysis with PROC MIXED of SAS and the means were compared by Fisher’s test at 5%. The more intensified systems presented higher values of performance variables, carcass characteristics, meat quality, and lower intensity of CH4 emissions demonstrating the potential of recovering and intensifying pasture-based systems under tropical conditions.